Effects of nonprotein nitrogen source in blocks on rumen parameters of steers fed prairie hay - Löest, C.A.; Lambert, B.D.; Trater, A.M.; Titgemeyer, Evan C.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Six ruminally cannulated steers (1012 lb) were fed prairie hay ad libitum supplemented with cooked molasses blocks that contained either 60% crude protein 83% of which came from urea (UREA block) or 60% crude protein with 42% from urea and 42% from biuret (UREA/BIURET block). Blocks were broken into small pieces to facilitate consumption and were fed once daily at .125% of body weight. Rumen samples were collected on days 3, 7, 14, and 21 at 0, 1, 2, 4, 6, 8, 12, and 16 hours after feeding blocks. Averaged over time, ruminal ammonia and total volatile fatty acid concentrations and plasma urea concentrations were lower (P<.05) for steers fed the UREA/- BIURET block than for those fed the UREA block. Acetate and propionate concentrations followed patterns similar to those of total volatile fatty acids, whereas butyrate increased rapidly after block consumption. Release of ammonia from biuret was not demonstrated clearly. Ruminal ammonia concentrations were no greater with the UREA/BIURET block at times distant from feeding than with the UREA block.
Keywords: Beef; Steers; Forages; Urea; Biuret